Babesia microti Infection Inhibits Melanoma Growth by Activating Macrophages in Mice - Shu, Xiang; Nie, Zheng; Luo, Wanxin; Zheng, Yaxin; Han, Zhen; Zhang, Hongyan; Xia, Yingjun; Deng, Han; Li, Fangjie; Wang, Sen; Zhao, Junlong; He, Lan (Frontiers in Microbiology, 2022)
Babesia microti is an obligate intraerythrocytic protozoan transmitted by Ixodes tick. Some protozoan infections, including Plasmodium yoelii, and Toxoplasma gondii, could significantly inhibit tumor development, due to producing antitumor effect by activating the immune response. Th1 immune response and macrophages are indispensable key factors in Babesia infection control. While Th1 immune response and macrophages also play an important role in regulating tumor development. In this study, B. microti was used to treat melanoma-bearing mice. It was found that B. microti infection can inhibit the growth of melanoma and increase the survival period of tumor-bearing mice. B. microti infection significantly enlarged the size of spleens in mice, analysis of immune cells in mouse spleens showed that the number of macrophages and CD4+ T cells was significantly increased in the tumor-bearing mice infected with B. microti compared to uninfected tumor-bearing mice, and the proportion of CD4+ T cells and M1 macrophages in the tumor was also increased. Immunohistochemical assays showed that B. microti infection inhibited tumor angiogenesis. Meanwhile, it was found that both B. microti and culture supernatant of B. microti could significantly induce the mRNA expression of iNOS, IL-6 and TNF-α in macrophages. The culture supernatant of B. microti could also convert IL-4-induced M2 macrophages to M1 type. In summary, B. microti exerted antitumor effects by stimulating the immune system of tumor-bearing mice and inducing immunosuppressive M2 macrophages to pro-inflammatory M1 macrophages. This study provides a new idea for the further study of the immune relationship between B. microti and host.